CONTOH BAHAN RUJUKAN UMUM DAN KHUSUS - Alfarrah Nazrah Felisha (JURNAL ILMIAH RESEARCH STUDENT, 2025)
General and special reference materials are a unity in the library, in this case to know the difference between these two things it is necessary to understand examples of these two things. Therefore, by knowing the differences, you can understand more deeply about these two materials.